Single‐crystalline porous NiO nanobiscuits with prompt adsorption activity for Congo red. (1st December 2017) - Hu, Hanmei; Wang, Man; Xuan, Han; Zhang, Kehua; Xu, Juanjuan
Abstract : Single‐crystalline two‐dimensional (2D) nickel oxide (NiO) porous nanobiscuits with diameters of 100–210 nm, thicknesses of 10–20 nm and pore sizes of <20 nm are fabricated through a low‐cost water bath combined with calcination treatment approach. The composition and morphology of the products are characterised by X‐ray diffraction, field‐emission scanning electron microscopy, transmission electron microscopy (TEM), high‐resolution TEM, selected area electronic diffraction and N2 adsorption/desorption. The possible formation mechanism of single‐crystalline porous NiO nanobiscuits is simply discussed. Served as adsorbent, the as‐prepared single‐crystalline porous NiO nanobiscuits exhibited excellent performance for the fast removal of Congo red from water, which is far beyond the adsorption rate of activated carbon. The results show that the adsorption isotherm fits well with Langmuir adsorption model. The maximum adsorption capacity is calculated to be 193.2 mg g −1, which is larger than that of other reported 2D NiO architectures.